When Co-Occurring Factors Impact Adult Learners: Suggestions for Instruction, Preservice Training, and Professional Development. Issue 1 (February 2020) - Housel, David A.
This literature review explored areas that are often manifest in adult classrooms but insufficiently addressed or overlooked in preservice training and in-service professional development for educators of adults. Three overarching themes emerged: (a) educational background considerations (e.g., significant interruptions in formal education), (b) disability considerations (e.g., learning disabilities and students on the autism spectrum), and (c) status considerations (e.g., domestic violence and mental health issues). This overview of the identified themes was contextualized within andragogy, which posits ways that adults learn differently from children. Recommendations to enhance instructional approaches were interwoven throughout the review. Following the overview and instructional recommendations, preliminary assertions for strengthening preservice training and ongoing professional development for educators of adults and areas for future research were advanced.